Analysis of STEM Components and Scientific Literacy in the 8th Grade Science Book on Energy Material - Intan Indiati; Siti Patonah; Harto Nuroso; Ummi Kaltsum (Postgraduate, University of Mataram, 2025)
This research lays the groundwork for developing an integrated STEM-based science e-module on energy material for Grade VIII students. The study aims to analyze the presence of STEM components—science, technology, engineering, and mathematics—and scientific literacy in Grade VIII science textbooks covering energy topics. Using a qualitative case study approach, the research examines the energy material presented in the Grade VIII science textbook published by the Center for Books, Ministry of Education, Culture, Research, and Technology. The analysis reveals that the science component dominates the discussion, while technology, engineering, and mathematics are largely absent. Regarding scientific literacy, the textbook presents energy concepts primarily by explaining science as knowledge and its applications in society. However, elements related to scientific inquiry, historical contributions, and science as a way of thinking are not integrated into the material